Effectiveness of buttress wall in reducing wall deflection for deep excavation supported by tied-back retaining wall systems: English - Abdi, Ari Surya; Prakasa, Muhammad Dwiyanto Agung (Himpunan Ahli Teknik Tanah Indonesia, 2025)
This study evaluates the effectiveness of buttress walls (BWs) in reducing wall deflection and ground anchor force in deep excavations supported by tied-back retaining systems. A three-dimensional finite element model (3D FEM) was employed for the study. First, a well-documented excavation project located in Vietnam that adopted BW in combination with ground anchors was first back-analyzed to validate the numerical model. The results showed good agreement between computed wall deflections and field measurements across all excavation stages. In the Vietnam case study, the BW was temporary and was demolished after the final excavation stage. The ground anchors installed were to limit the wall deflection during BW demolition. Parametric studies were then conducted to assess two BW configurations: inner BW (I-BW), placed within the excavation area (Vietnam case), and outer BW (O-BW), located behind the retaining wall. The two configurations were analyzed with and without ground anchors. In addition, one run with only ground anchors was conducted to evaluate the effectiveness of BW vs. ground anchors. Results show that both BW configurations reduced wall deflections and anchor forces, with O-BW performing slightly better in the absence of ground anchors due to additional frictional resistance between the BW and the retained soil throughout excavation stages. When ground anchors are used, the difference in performance between I-BW and O-BW becomes negligible due to increased system stiffness. For wall retained by ground anchors only, the deflection of wall is flexible, whilst wall retained by BW only shows rigid behaviour. The maximum deflection, however, is of similar magnitude when the wall is retained by O-BW only and ground anchors only. The deflection is slightly larger when retained by I-BW only. The findings highlight the potential of combining BWs with anchors to increase the rigidity of structural system and enhance excavation safety, particularly under complex soil conditions